Indicator Absorbance Spectra and Ligand Complexation Ratio with Metal Ions - Farasram, Rakesh; Farasram, P.L.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Three reagents β-arylaminocrotonophenylhydrazides were prepared andtheir ML and ML2 complexes of copper(II) and mercury(II) ions wereprepared. Their compositions were studied by usual methods.Spectrophotometric study can only be employed for coloured complexesby Job, Mole ratio and slope ratio methods. In this communicationspectrophotometic study of above complexes was done by a novel dyeindicator method for composition study of coloured copper complex andcolourless mercury complex by monovariation method.